Islamic Ethnoeducation On Traditional Games From The Kaili Tribe Of Palu City - Marwany (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
The traditional games of kaili children, nogarata, nomaca, and gunrece, are formed from socio-cultural processes influenced by the spirit of Islam. His paradigm of play shifted from the sacred and mystical to the educational and Islamic paradigm that positioned traditional games as a vehicle for educating and shaping morals. The purpose of this study is to find, identify, and explain the traditional game paradigm of the Kaili tribe in the context of sociocultural, educational, and Islamic (Islamic ethnoeducation). The method used in this study is a qualitative descriptive method that aims to obtain and obtain the results of phenomena in aspects of Islamic ethnoeducation in the traditional game of the Kaili Tribe. Intensive data collection is carried out with engaged observation, interviews and documentation. Data analysis is performed using ethnographic principles through domain analysis, taxonomic analysis, and component analysis. The result of his research is that the traditional games of the Kaili people, nogarata, nomaca, and gunrece, are formed and distributed in socio-cultural, educational, and Islamic dynamics. Socio-culture is a source of creation and value systems; education becomes the pragmatics of the use of traditional children's games for teaching or educational purposes; while Islam became an identity that changed the socio-cultural paradigm and became an important value system in the traditional game of the Kaili Tribe. With the Islamic paradigm, the traditional game of Kaili tribe children becomes a game carried out with the aim of distributing and internalizing Islamic values, especially in the good morals of children.